DISCOURSE OF HADITH’S HERMENEUTIC: Limitations and Terms of Application for Applying Five Hermeneutical Approach (RIWAYAH, 2024)
The model of hadith Hermeneutics has been applied by some contemporary scholars attracting attention to be studied scientifically, as there is already a method of understanding hadith called syarh hadits in the study of ‘Ulumul Hadits. So the purpose of this study is to discuss the limitation of the application of the hermeneutic approach to hadith as well as to examine the position of hermeneutics in the minds of Islamic academics. The research method is qualitative research, then references from books (library research). The results of the study concluded that hermeneutics of hadith can be used in understanding hadith, although it is still within the scope of ta’wil and is not the main reference in understanding the text of the Prophet’s hadith. Hermeneutics is seen as an explanatory tool for religious texts that can still be used with restrictions and conditions not to demonize religious values, but Islamic methods such as Syarhu Hadist in ‘Ulumul Hadist remain the main reference in interpreting hadith texts. The author recommends strengthening Islamic knowledge before using hadith hermeneutics, in order to guard against errors in understanding hadith such as Jarh wa Ta’dil, ‘Rijalu al-Hadith, Nasikh wa Mansukh Al-Hadith and ect. [Model Hermeneutika Hadis telah diterapkan oleh beberapa ulama kontemporer menarik perhatian untuk diteliti secara ilmiah, sebagaimana sudah ada sebuah metode memahami hadis yang disebut dengan syarh hadits dalam kajian ‘Ulumul Hadits. Sehingga tujuan penelitian ini untuk membahas batasan penggunaan pendekatan hermeneutika terhadap hadis sekaligus meneliti kedudukan hermeneutika dimata akademisi islam. Metode penelitian ini adalah kualitatif yang termasuk pada kajian kepustakaan (library research). adapun Hasil penelitian menyimpulkan bahwa hermeneutika hadis dapat digunakan dalam memahami hadis, meskipun masih dalam cakupan ta’wil dan bukan rujukan utama dalam memahami teks hadis Nabi. Hermeneutika dilihat sebagai alat penjelasan terhadap teks keagamaan yang masih boleh digunakan dengan batasan dan syarat tidak untuk menjelek-jelekkan nilai keagamaan, adapun tetapi metode islam seperti syarh hadits dalam ‘Ulumul Hadits tetap menjadi acuan utama dalam interpretasi teks hadis. Penulis merekomendasikan untuk memperkuat keilmuan islam sebelum menggunakan hermeneutika hadis, agar dapat menjaga kesalahan dalam pemahaman hadis seperti Ilmu Jarh Wa Ta’dil, ‘Ilmu Rijalu Al-Hadits, Nasikh wa Mansukh Al-Hadits dan lain sebagainya.]